A construção de saberes na formação de psicólogas(os) no Brasil: presença e silenciamento das relações étnico-raciais - Martins, Flavia Regina Sousa (Universidade do Vale do Rio dos Sinos, 2025)
Discussions on ethnic-racial issues have challenged knowledge production in Brazil and revealed gaps in Psychology education, whose curricula remain predominantly guided by Eurocentric epistemologies. This study aimed to understand how ethnic-racial themes are addressed in institutional and curricular documents of Psychology programs at Brazilian federal public universities. Institutional Development Plans (PDIs) and Pedagogical Course Projects (PPCs) from five federal universities, one in each region of the country, were analyzed through documentary analysis inspired by the Foucauldian conception of documents as discursive practices, articulated with decolonial and Afrocentric perspectives. Theoretical references included authors such as Conceição Evaristo, Lélia Gonzalez, Nilma Lino Gomes, Frantz Fanon, and Molefi Kete Asante. Results indicate that PDIs address diversity in a generic manner, often linked to access and retention policies, without effectively guiding formative proposals to confront structural racism. PPCs show occasional inclusion of disciplines, references, and research lines related to the theme, without establishing it as a structuring axis of training. It is concluded that the discussion of ethnic-racial issues, marked by presences, absences, and silences, evidences the hegemony of a white and Eurocentric rationality and demands an epistemological repositioning grounded in decoloniality and Afrocentricity, capable of promoting critical psychological education committed to antiracist transformation.
Keywords: Psicologia; Relações raciais; Decolonialidade; Afrocentricidade; Formação de psicólogas(os); Psychology; Racial relations; Decoloniality; Afrocentricity; Psychology education; ACCNPQ::Ciências Humanas::Educação